Assessment of Plasma Level of CTHRC-I in Patients with Rheumatoid Arthritis - Sahar Alwan; Raja Abdul-Ridha; Alaa Ali (The Iraqi Journal of Medical Sciences, 2021)
Background: Rheumatoid arthritis (RA) is a chronic progressive, autoimmune disease that affects about 1.5% of the community. New markers are needed for early diagnosis of RA as seronegativity in early RA remains a major limitation of both anti-citrullinated protein antibodies (ACPA) and rheumatoid factor (RF). Objective: To measure the plasma levels of the collagen triple helix, repeat containing-1 (CTHRC-1) protein in RA patients. Methods: 103 RA patients (56 new diagnostic without treatment group and 47 patients on treatment were included in this study according to American College of Rheumatology (ACR) criteria, in addition to 25 subjects as healthy control group. CTHRC-1 level was measured by using Immunoassay System in plasma samples. Results: The mean and SD of CTHRC1 was (49.10±6.51 ng/ml) in RA patients was significantly higher than its mean in healthy controls (6.20±2.81 ng/ml), (p value =0.002). The distribution of CTHRC1 was insignificantly associated with patient treated or not (P value 1.000, 0.273) respectively, or were the patients had positive or negative RF (P value 0.118, 1.000) respectively. Conclusion:sing the Immunoassay System for CTHRC-1 quantification, CTHRC1 could be used as a plasma marker that can aid in the diagnosis of RA although it has no association with seropositivity with RF or treatment. Keywords: Collagen triple helix repeat containing-1, rheumatoid arthritis, serum rheumatoid factor, anti-CCP Citation: Alwan SA, Abdul-Ridha RA, Ali AI. Assessment of plasma level of CTHRC-I in patients with rheumatoid arthritis. Iraqi JMS. 2021; 19(2): 189-193. doi: 10.22578/IJMS.19.2.8